Analysis of Availability, Quality, and Price of Food Options in Denver, CO Grocery Stores. Issue 3 (4th May 2021) - Lunsford, Jesse; Brunt, Ardith; Foote, Jerald; Rhee, Yeong; Strand, Mark; Segall, Mark
ABSTRACT: This study examined Denver, Colorado area grocery stores to identify if significant differences in food price, availability, or quality existed for different population groups. Thirty stores were randomly selected and analyzed using Nutritional Environmental Measure Survey for Supermarkets (NEMS-S). Results showed there was no significant relationship between availability or quality and socioeconomic status or minority status. Higher prices were seen in stores of higher total income. Large supermarkets offered higher quality produce. Further research should assess how consumers make a store and consequent purchasing decisions as there are mixed results in the connection between access to healthful food choices and health.